2018
DOI: 10.1007/s11136-018-1903-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life of children and adolescents with and without migration background in Germany

Abstract: Children and adolescents with double-sided migration background have poorer OHRQoL than comparably aged migrants with single-sided migration background or non-migrations. Between-group differences in OHRQoL could not be sufficiently explained by effects of socioeconomic status or physical oral health characteristics. Thus, other methodological, cultural, or immigration-related factors might also play an important role for the observed effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…The growing concern for oral health as part of general health, and the new concept of impacts of oral diseases on quality of life, is gaining global attention. However, in many deprived communities, and low‐ and middle‐income countries, the matter is either not sufficiently studied or findings not sufficiently implemented, adding supportive evidence on disparities in outcomes of OHRQoL …”
Section: Introductionmentioning
confidence: 99%
“…The growing concern for oral health as part of general health, and the new concept of impacts of oral diseases on quality of life, is gaining global attention. However, in many deprived communities, and low‐ and middle‐income countries, the matter is either not sufficiently studied or findings not sufficiently implemented, adding supportive evidence on disparities in outcomes of OHRQoL …”
Section: Introductionmentioning
confidence: 99%
“…Differences in OHRQoL were also found between Hispanic and white elderly in the US [ 36 ]. Recently, differences in OHRQoL were studied between groups with and without a migration background, in a German population which was based on clinical orthodontic patients and students [ 37 ]. In accordance with our study, they have shown that children and adolescents with a migration background score lower OHRQoL than non-migrants, which was partly explained by socioeconomic and oral health status.…”
Section: Discussionmentioning
confidence: 99%
“…Dünya çapındaki yüksek göç oranı göz önüne alındığında, göç geçmişi olan kişilerde ağız hastalıklarının önlenmesi, özellikle çocuklar ve ergenler için önemli bir halk sağlığı sorununu temsil etmektedir (10). Sosyoekonomik durumun yanı sıra, köken, kültür ve çevresel faktörlerden de etkilenen ağız sağlığı konusunda pek çok araştırma yapılmıştır (7)(8)(9)(10).…”
Section: Göçmen çOcuklardaki̇ Ağiz Sağliği Araştirmalariunclassified
“…Almanya'da yapılan bir araştırmada göçmen çocuklar iki grupta sınıflandırılmıştır: (i) bir ebeveyn yabancı bir ülkede doğmuş (tek taraflı göçmen geçmişi) ve (ii) her iki ebeveyn ve/veya kendisi yabancı bir ülkede doğmuş çocuk (çift taraflı geçiş geçmişi). Çift taraflı geçmişi olan çocukların ve ergenlerin ağız sağlığı ile ilgili yaşam kalitesinin tek taraflı olanlara göre daha düşük olduğu görülmüştür (10). Amerika Birleşik Devletleri'nde yapılan bir çalışmada yine göçmen nüfusta ağız ve diş sağlığının belirgin olarak düşük olduğu bulunmuş ve bu göçmenler arasında da farklı ırklar arasında ciddi bir fark göze çarpmıştır (16).…”
Section: Farklı Göçmen Gruplar Arasındaki Farklılıklarunclassified